Demystifying confidence in different levels of the police: evidence from Shanghai, China - Zhang, Shan-gen (Policing and society, 2020)
Extending Fei's ‘differential mode of association’ (1992) and Cao et al.'s argument that Chinese trust is layered and hierarchical (2015), this study explores the differential confidence in the different levels of police agencies and brings various forms of trust into the study of confidence in the police. Results from a household random sample reveal that Shanghainese make a distinction between hierarchical levels of the police. Their confidence level toward their municipality police department is similar to that toward the Ministry of Public Security while their confidence levels toward the police at stations and Paichusuo are more alike. In addition, the multi-variate regression analyses indicate that institutional trust is the dominant factor for explaining confidence in both local and upper-level police. Media trust, sense of safety, financial satisfaction and collectivism are significant predictors in both models. Obeying the law, gender and class influence confidence in the local police but not the upper-level police while intermediate trust and education have a significant effect only on confidence in the upper-level police. It is concluded that assessment of local police is central to the understanding of public confidence in China.